Seznami odpisanega gradiva za Narodno in univerzitetno knjižnico v obdobju 2011-2016 - Poličnik-Čermelj, Tereza (Knjižnica, 2017)
Purpose: Since 2005, the National and University Library (NUL) has been systematically building its collection by materials withdrawn from other Slovenian libraries. It selects ''slovenica'', and ''jugoslavica'' published until 1991 from the lists of withdrawn materials from all types of libraries. Since 2014, the COBISS system has been providing an automatic comparison of the volumes data and NUL holdings when the lists of withdrawn materials are prepared as a defined computer print-out. If the lists are not prepared by this tool, the possibility of error is greater, which is obvious by a big difference between the number of items sent to NUL and the number of items added to NUL collection. The paper aims to identify the reasons for this disproportion and the solutions on how the procedures could be improved to reduce the differences. Methodology/approach: The paper presents an analysis of the Slovenian libraries' weeding statistics and the records of the offered withdrawn materials and the volumes actually sent to NUL. The data on weeding statistics was collected by the Library System Development Centre, and the records on offered and sent material were kept by the Acquisition Department at NUL during the period 2011-2016. Results: In this period, the results showed that all public libraries deselected library materials but only half of them deselected the obsolete materials which would be useful for NUL collection. Deselection of materials was carried out in 55% of higher- education libraries of which only 14% deselected the obsolete materials useful for NUL collection, and in 29% of special libraries of which only 10% deselected the obsolete materials. For school libraries, the data have been collected only for 2016. 72% of school libraries deselected materials of which 6% deselected the obsolete materials useful for NUL collection. NUL has selected only 4% of all the titles on the lists of withdrawn materials. The time needed to check the titles from the lists in the catalogue and to process the received material was calculated. Research limitation: As there are no similar models of acquisition in other national libraries, the study is limited to Slovenian libraries. Originality/practical implications: The study answers the question of whether or not the Library should continue to build the national collection in this way. Another possibility would be to accept only the defined computer print-outs.
Keywords: Slovenian libraries; slovenske knjižnice; odpis gradiva; withdrawals; nacionalne knjižnice; national libraries; acquisition; nabavna politika; statistical analysis; statistične analize